Equilibrium Effects of Health Care Price Information - Brown, Zach Y. (The Review of Economics and Statistics, 2019)
Abstract Do information frictions in health care markets lead to higher prices and price dispersion? Focusing on medical imaging procedures, this paper examines the equilibrium effect of a unique statewide price transparency website. Price information leads to a shift to lower-cost providers, especially for patients subject to a deductible. Furthermore, supply-side effects play a significant role in the long run, benefiting all insured individuals. Supply-side effects reduce price dispersion and are especially relevant in concentrated markets. These effects are important given that high prices are thought to be a primary cause of high private health care spending.